2009
DOI: 10.1073/pnas.0906593106
|View full text |Cite
|
Sign up to set email alerts
|

A chemical-genetic approach to study G protein regulation of β cell function in vivo

Abstract: Impaired functioning of pancreatic ␤ cells is a key hallmark of type 2 diabetes. ␤ cell function is modulated by the actions of different classes of heterotrimeric G proteins. The functional consequences of activating specific ␤ cell G protein signaling pathways in vivo are not well understood at present, primarily due to the fact that ␤ cell G protein-coupled receptors (GPCRs) are also expressed by many other tissues. To circumvent these difficulties, we developed a chemicalgenetic approach that allows for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
382
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 304 publications
(408 citation statements)
references
References 26 publications
21
382
2
3
Order By: Relevance
“…While it has been shown that CNO is not significantly back metabolized to clozapine in mice, it is possible that the limited clozapine produced is sufficient to induce DREADD activity reported in Gomez et al, while being subthreshold for off-target effects (Guettier et al 2009). Moreover, while it has been demonstrated that systemic clozapine is able to induce changes in neural activity, these changes occur in response to significantly higher doses (35 mg/kg) than what could be back metabolized from our doses of CNO (3 mg/kg) (Werme et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…While it has been shown that CNO is not significantly back metabolized to clozapine in mice, it is possible that the limited clozapine produced is sufficient to induce DREADD activity reported in Gomez et al, while being subthreshold for off-target effects (Guettier et al 2009). Moreover, while it has been demonstrated that systemic clozapine is able to induce changes in neural activity, these changes occur in response to significantly higher doses (35 mg/kg) than what could be back metabolized from our doses of CNO (3 mg/kg) (Werme et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…We first utilized chemogenetics to selectively control generic Gαs signaling in excitatory neurons of the BLA through the use of the Gαs DREADD rM3Ds (designer receptors exclusively activated by designer drugs) (Armbruster et al, 2007;Farrell et al, 2013;Guettier et al, 2009). Here we show that activation of generic Gαs signaling via within the BLA is sufficient to induce acute and social anxiety-like behavioral states.…”
Section: Introductionmentioning
confidence: 99%
“…Like optogenetics, designer receptor exclusively activated by designer drug (DREADDs) can either activate or silence neurons. The first DREADD system mutated the muscarinic acetylcholine receptor so that it is only activated by clozapine-N-oxide, an inactive metabolite of the central nervous system drug clozapine [146,148,149]. The muscarinic DREADD receptor is coupled to Gq, which is an excitatory channel that depolarizes neurons and enhances their excitability through phospholipase C [146,150].…”
Section: Designer Receptor Exclusively Activated By Designer Drugmentioning
confidence: 99%
“…The muscarinic DREADD receptor is coupled to Gq, which is an excitatory channel that depolarizes neurons and enhances their excitability through phospholipase C [146,150]. A chimeric muscarinic-adrenergic receptor DREADD known as GsD also activates neurons but via cyclic adenosine monophosphate-mediated signaling [149,151]. In contrast, the human M4 muscarinic DREADD receptor is coupled to Gi and leads to neuronal silencing through opening inwardly rectifying potassium channels [146].…”
Section: Designer Receptor Exclusively Activated By Designer Drugmentioning
confidence: 99%